Advances in global land use systems development and sustainability: A bibliometric analysis - Isaac Sarfo; Jiajun Qiao; Nana Adwoa Anokye Effah; Emmanuel Yeboah; Philip Kofi Alimo; Dhekra Ben Amara; Clement Kwang; Zhu Qiankun; Michael Kpakpo Allotey; Michael Atuahene Djan (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: Land-use systems have a significant impact on environmental, economic, and societal issues worldwide. With agricultural activities, urban development, and conservation efforts, the complex nature of land use influences key global challenges, including climate change, food security, and biodiversity loss. As the world confronts these issues, it is essential to understand the trends, innovations, and emerging frontiers in land use systems. These developments not only reflect the evolving relationship between humans and the environment but also offer potential pathways toward sustainability and resilience.